Probiotic and Lifestyle Modification in Obese Pediatrics with Non-Alcoholic Fatty Liver Disease - Goyal, Pooja; Thapa, Babu Ram; Sharma, Neeta Raj; Bhatia, Anmol (Indian Journal of Community Health, 2019)
Background: Non alcoholic fatty liver disease is an upcoming causes of chronic liver disease in pediatric population in Asia. Aims & Objective: To evaluate the potential of probiotic VSL#3 and Lifestyle modification in obese pediatrics with Non alcoholic fatty liver disease (NAFLD). Material & Methods: we conducted clinical trial in 106 obese children in age group of 5 to18 years and divided in to four groups;VSL#3 plus lifestyle intervention (n=26), VSL#3 (n=27), Lifestyle intervention (n=26) and Placebo (n=27) received interventions for four months. To identify NAFLD by ultrasonography, Body mass index (BMI), mid arm circumference (MAC), waist circumference (WC) and triceps skinfold thickness (TSF) were done. Serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), low-density lipoprotein cholesterol(LDL-c),high-density lipoprotein cholesterol (HDL-c), triglyceride (TG), cholesterol, fasting blood glucose(FBG), high sensitivity C-reactive protein (HSCRP), uric acid, obesity hormones were measured along with their dietary intake at baseline and post trial. Results: VSL#3 plus lifestyle intervention significantly the most pronounced therapy for reducing fatty liver grades, anthropometric with biochemical parameters and beneficial impact on obesity hormones (p<0.001) as compared to single therapy of VSL#3 and lifestyle intervention alone. Conclusion: Combined therapy of VSL#3 plus lifestyle intervention is promising treatment for management of NAFLD in Indian obese children.